The Impact of Multimodal Prehabilitation on the Incidence of Postoperative Complications in Patients Undergoing Colorectal Cancer Resection: A Narrative Review - Sordyl, Katarzyna; Grzelak, Oliwia; Bolek, Oliwia; Rogulski, Krzysztof; Fengier, Maria; Kuśmierczyk, Weronika; Majkowska, Magdalena; Szczepański, Piotr; Kącikowska, Justyna; Trzaskowski, Jakub (Journal of Education, Health and Sport, 2026)
Background Colorectal cancer (CRC) resection imposes profound physiological stress, often leading to acute catabolism, immunosuppression, and a drastic decline in functional capacity. While Enhanced Recovery After Surgery (ERAS) protocols have revolutionized intra- and postoperative care, multimodal prehabilitation capitalizes on the preoperative window. By integrating physical therapy, targeted nutritional support, psychological interventions, and medical optimization, this approach aims to maximize the patient’s physiological and psychological reserves prior to surgical trauma. Aim To evaluate the efficacy of multimodal prehabilitation in mitigating postoperative complications in CRC patients and to assess the physiological foundations and methodological challenges present in current literature. Materials and methods: This narrative review was conducted using articles sourced from PubMed by keywords: colorectal cancer, colorectal surgery, multimodal prehabilitation, postoperative complications, ERAS. We examined randomized clinical trials, observational studies, meta-analyses published between 2021-2026. Due to the narrative nature of this review, study selection was based on thematic relevance rather than strict methodological criteria. Results: The majority of studies included in this review demonstrated that multimodal prehabilitation significantly reduces the incidence of postoperative complications in patients undergoing colorectal cancer (CRC) resection. Conclusions: Multimodal prehabilitation proactively optimizes functional and immunological reserves, reducing the incidence of postoperative complications. However, considerable methodological heterogeneity persists across trials regarding intervention duration, adherence to FITT principles, and evaluation metrics. Future high-quality research must standardize protocols and assessment tools to facilitate the routine integration of prehabilitation into perioperative care.